Mapping theme trends and knowledge structures of dignity in nursing: A quantitative and co‐word biclustering analysis - Liu, Yujia; Li, Xiaohan; Ma, Li; Wang, Yanjie (Journal of advanced nursing, 2022)
Aim The present study aims to explore the research hot spots, development trends and knowledge structure of dignity in the nursing field. Design Quantitative and co‐word biclustering analysis were used. Methods Articles on dignity care published from 01 Jan 2011 to 31 Dec 2020, were retrieved from PubMed. The extracted Medical Subject Headings (MeSH) terms were quantitatively analysed using Bibliographic Item Co‐occurrence Matrix Builder software. To determine the hot spots, a biclustering analysis was completed using gCluto1.0 software. A strategic diagram and a social network analysis (SNA) were used to reveal trends in the theme and knowledge structure. Results In the parameters of the retrieval strategy, a total of 1977 papers were included in the present study. Amongst all the extracted MeSH terms, 27 high‐frequency MeSH terms were identified, and the hot spots were grouped into five categories. These were namely dignity in: (1) dementia care, (2) palliative care, (3) older people care, (4) healthcare and (5) clinical nursing. In the strategic diagram, the study of dignity in clinical nursing was active and should become an emerging field of research in the near future. Conclusions Based on the co‐word biclustering of dignity care over the past 10 years, five hot spots were identified, and it was predicted that research on dignity in clinical nursing would be the main trend in future studies. Amongst the five themes it was interesting to note that dignity in dementia and palliative care are core priorities to which scholars should pay more attention. Impact In recent years, dignity‐conserving care has been highly valued, however, there are few relevant bibliometric articles that can be referenced on this topic. The present study was considered to offer novel insights into research on dignity in nursing and could be a reliable reference point for researchers when launching new projects.